Studies on High Density Polyethylene Reinforced with Phosphate Ore Particles: Thermal, Rheological, Mechanical and Morphological Properties. (21st November 2016) - Shaikh, H.; Anis, A.; Poulose, A. M.; Alam, M.; A-Otaibi, M. N.; Alam, M. A.; Al-Zahrani, S. M.
ABSTRACT: Calcareous phosphate ore can be utilized as a cost-effective alternate to other inorganic fillers for polymer-based composites. In this study, composites of high-density polyethylene and phosphate rock ore particles were prepared by melt blending and injection-molding techniques. The thermomechanical, rheological, and mechanical properties of these composites were studied to investigate the effect of filler loading on their functionality. The reduction in the crystallinity of phosphate ore/high-density polyethylene composites was observed compared to that of the neat high-density polyethylene. The relative crystallinity of the neat high-density polyethylene decreases from 53 to 30% by the addition of 2.5–15 wt% of ore, respectively. Comparison of the linear dynamic viscoelasticity for the neat high-density polyethylene and the ore-filled composites shows t a monotonic increase in both storage modulus and loss modulus with the increasing frequency. The viscoelastic behavior at high frequencies remains unaffected. However, at lower frequencies, both G ′ and G ″ exhibit diminished frequency dependence. It was also observed that higher filler content decreased the tensile and impact strength, whereas the Young's modulus of the composites increased. The morphological analysis shows relatively weak interaction between the fillers and the matrix because of agglomeration which in turn adversely affects the mechanical properties of the composites. GRAPHICAL ABSTRACT: